Comparative Study of Carbon Nanotubes and Lignosulfonate as Polyvinyl Acetate (PVAc) Wood Adhesive-Reinforcing Agents - Marcela Vidal-Vega; Mario Núñez-Decap; Javier Hernández-Durán; Pedro Catricura-Muñoz; Catalina Jara-Briones; Boris Moya-Rojas; Camila Opazo-Carlsson (Applied Sciences, 2023)
This study aimed to reinforce a polyvinyl acetate-D3 (PVAc-D3) adhesive to improve its mechanical and thermal properties. The goal was to reach a polyvinyl acetate-D4 (PVAc-D4) adhesive performance that could make PVAc-D3 more attractive and add value to wood products. PVAc-D3 was modified by adding 0.05% and 0.5% (wt.) of multi-walled carbon nanotube particles (MWCNTs) as well as 0.5% and 2.5% (wt.) of lignosulfonate (LIGNO) particles. Adhesive blends were compared to neat PVAc-D3 and PVAc-D4, evaluating their physical–chemical properties. Also, they were analyzed using Fourier transform infrared spectroscopy (FT-IR) and mechanical dynamic analysis (DMA) with a storage module (E′). The blends were used to fabricate laminated wood pieces, pressed at 60 and 120 min (min), to be tested at shear strength under dry, elevated temperature and vacuum-pressure conditions. Delamination and adhesive penetration were determined by microscopy. Incorporating fillers into PVAc resulted in a decrease in viscosity. FT-IR evidenced that the PVAc-D4 adhesive had a bigger cross-linked degree than the other adhesive samples. The DMA showed that LIGNO and MWCNT fillers help increase E′ at the bond line, reaching a higher stiffness level than neat PVAc-D3. In dry conditions, specimens glued with D3-LIGNO 0.5% at 120 min reached shear strengths that were 100%, 28%, and 3% higher than the standard requirement, PVAc-D4, and neat PVAc-D3, respectively. Also, those glued with D3-MWNTC 0.05% reached shear strengths that were 91%, 21%, and 3% higher than the standard requirement, D4, and neat D3, respectively. Only PVAc-D4 reached the standard requirement for elevated temperature and vacuum-pressure conditions. Delamination of ≤5% (standard requirement) was achieved by wood specimens glued with neat PVAc-D3, D3-MWNTC 0.5%, D3-LIGNO 0.5%, and PVAc D4 adhesive samples. In this study, it was found specific ranges of average penetration (AP) to ensure a glue line good quality. To conclude, LIGNO and MWCNT particles improved the PVAc-D3 adhesive’s performance in dry conditions, but they were not very relevant to the D3 adhesive’s behavior. At high temperatures, the LIGNO filler worked very well as a thermic stabilizer compared to the MWCNT filler. The solubility of the reinforcing agent can affect an adhesive’s blend quality and its cohesion properties. An adequate penetration depth procures a good quality bond between an adhesive and substrate with less possibilities of delamination. An extensive pressing time may cause a weak interphase and poor mechanical properties in an adhesive bond in the presence of humidity.